A Method for Rapid Polyethyleneimine-Based Purification of Bacteriophage-Expressed Proteins from Diluted Crude Lysates, Exemplified by Thermostable TP-84 Depolymerase - Beata Łubkowska; Edyta Czajkowska; Ireneusz Sobolewski; Natalia Krawczun; Agnieszka Żylicz-Stachula; Piotr M. Skowron (Microorganisms, 2023)
Purification of bacteriophage-expressed proteins poses methodological difficulties associated with the need to process entire culture medium volume upon bacteriophage-induced bacterial cell lysis. We have used novel capsule glycosylase-depolymerase (TP84_26 GD) from bacteriophage TP-84, infecting thermophilic Geobacillus stearothermophilus bacteria, as a representative enzyme to develop a method for rapid concentration and purification of the enzyme present in diluted crude host cell lysate. A novel variant of the polyethyleneimine (PEI)-based purification method was devised that offers a fast and effective approach for handling PEI-facilitated purification of bacteriophage-expressed native proteins. Due to the very basic nature of PEI, the method is suitable for proteins interacting with nucleic acids or acidic proteins, where either mixed PEI-DNA or RNA–protein complexes or PEI–acidic protein complexes are reversibly precipitated. (i) The method is of general use, applicable with minor modifications to a variety of bacteriophage cell lysates and proteins. (ii) In the example application, TP84_26 GD was highly purified (over 50%) in a single PEI step; subsequent chromatography yielded a homogeneous enzyme. (iii) The enzyme’s properties were examined, revealing the presence of three distinct forms of the TP84_26 GD. These forms included soluble, unbound proteins found in host cell lysate, as well as an integrated form within the TP-84 virion.